PENGARUH KOMUNIKASI KEPEMIMPINAN TERHADAP EFEKTIVITAS KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA JAMBI - Nevi Ariessetyawati; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Leadership has a great influence on all the company's employees, leadership is an attempt to influence others to achieve goals. How to influence people with the instructions or commands, actions that cause others to act or respond and lead to positive changes, an important dynamic force that motivates and coordinates the organization in order to achieve the goal, the ability to create confidence and support among subordinates so that the organization can be achieved. In accordance with the stimulus response theory assumes leadership can be regarded as a way of leadership in directing, encouraging and manage all the elements in the group or organization to achieve an organization's desired goal to produce maximum employee.The method used in this research is quantitative method, and researchers collected data using a questionnaire. The location is on the street of Jend. A Thalib Pematangsulur Telanaipura Jambi. The number of samples is 85 respondents obtained from census formula. To determine the influence of these variables, researchers used a simple linear regression analysis. As for the processing of the questionnaire test, performed using the statistical program product and service solution (SPSS) Windows version 16.From Communication variables influence of strong leadership is the delivery of orders and instructions through oral or written work effectively (92.9%), while the effectiveness of a strong employee absenteeism presence is very important in establishing the discipline of work (91.8%). These results indicate that the influence of leadership communication on the effectiveness of employees working in the tax office pratama jambi, that the value of R = 0.742 and the coefficient of determination (Rsquare) is approximately 0.694 outcome of squared correlation coefficient of 0.343 x 0.343 with a significant level of 0.002 is smaller than a = 0.05. The figure shows the understanding that the contribution of leadership communication influence on the effectiveness of employee obtained amounted to 69.4% with strong influence category.Keyword: Leader communication, effectivity and employees concept